Proximate composition, amino acids, fatty acids and mineral content of unexplored wild edible mushrooms of Odisha: wild edible mushrooms of odisha - Rajoriya, Ashutosh; Tripathy, Sushree Shant; Gupta, N. (Mushroom Research, 2023)
Abstract: Wild edible mushrooms are considered as very good source of minerals and nutrients. The present study was conducted to evaluate proximate composition of macro and micro nutrients of nine most popular wild edible mushrooms of Odisha (Termitomyces clypeatus, T. eurrhizus, T. heimii, Russula brevipes, R. nigricans, Lentinus fusipes, L. tuberregium, Volvariella volvacea, Tuber rufum). Protein, total carbohydrate, reducing Sugar, non reducing sugar, ash, cholesterol and total fiber contents ranged from 0.80-20.53 mg/g, 19.16-38.77 g/100g, 5.55-16.25 mg/g, 18.72-37.56 g/100g, 3.63-7.36 %, 0-2.44%, 1.92-4.34% respectively on dry wt basis. All the mushrooms contained large amount of free amino acids, fatty acids and vitamins. In addition to that the sample studied were exhibiting large amount of mineral nutrients too. The finding shows that the indigenous variety of mushrooms commonly palatable in Odisha can be used not only as a nutritious food but also for the pharmaceutical values.